Implementation of a Hospital-Based Home Palliative Care at regional level: A quantitative study of the Ospedalizzazione Domiciliare Cure Palliative Oncologiche program in Lombardy. (March 2015) - Masella, Cristina; Garavaglia, Giulia; Borghi, Gabriella; Castelli, Alberto; Radaelli, Giovanni; Peruselli, Carlo
Background: Home Palliative Care services can overcome trends of institutionalized dying and support higher rates of death at home. Home Palliative Care services rarely scale-up into regional health planning. This generates unwarranted variability in service provision and outcomes across patients. Lombardy Region sponsored a Hospital-Based Home Palliative Care program, which implemented a common service to oncological patients in the territory, with the purpose to align hospitals toward a target of 65% deaths at home. Aim: Our work assesses service characteristics and outcomes achieved by the regional program from 2009 to 2011. Design and setting: Descriptive analysis from an institutional database of service characteristics, regional expenditure, and outcomes (temporary hospitalization and patient discharge) representing 11, 841 patients served by 24 providers in the period 2009–2011. Results: Targets of 65% deaths at home were achieved across the Region, with temporary re-hospitalization below 4.4%. The average pathway length stood above 1 month; intensity of care stood above ministerial and regional standards, with most home visits performed by nurses and physicians. Conclusions: The implementation of the regional program revealed three strengths (prompt identification and enrollment of eligible patients, and quantity of home visits) and two weaknesses (limited enrollment from general practitioners and multi-disciplinarity). This highlights opportunities for policy-makers to invest on regional protocols of Hospital-Based Home Palliative Care to reduce trends of institutionalized dying and align providers to homogeneous results.